Teacher Research as a Means to Create Teachers' Communities in Inservice Programs - Melba Libia Cárdenas (Asociación Colombiana de Profesores de Ingles, 2016)
Teachers' professional development programs should fulfill three key requirements: updating, innovation and research. Therefore, universities should make plans to respond to those parameters. In addition, a common concern among teachers and educational authorities nowadays is the develpment of students' competencies. In view of this, classroom teachers and universities have stressed the need of thinking about teachers' competencies and ways to facilitate or bring about teacher change and better teaching performances. In this article, I will refer to teachers' communities or teacher study groups as a way to foster teacher development and teacher research.